Efektifitas Pengelolaan Dana Desa Berdasarkan UU No. 6 Tahun 2014 - Berutu, Ermita; Iskandar, Adetya; Tamba, Sri Milka Ulinasari; Saragih, Ruth Sayeta; Sinaga, Juni Atia Intan Sari; Siagian, Jhonathan; Ginting, Eka Zefanya; Ivanna, Julia (Journal of Law & Policy Review, 2024)
This article or article aims to determine the effectiveness of village fund management based on Law No.6 of 2014. The problem is focused on managing village funds that are not running well. To approach this problem, theoretical reference is used theoretical references are used from journal and ebook reference sources and use literature studies. . The data is collected through library research often referred to as library research, which is a series of activities related to library data collection methods. The main data source in this study is a collection of several journals and books indexed nationally and internationally which are recognized in addition to academic references. which concerns the subject containing a discussion of the effectiveness of village fund management based on uu no. 6 of 2014 and analyzed qualitatively. This study concludes that Law Number 6 of 2014 is a source that is used as a guide in village implementation, including the Village Fund policy which has been implemented from the 2015 fiscal year to the present. The implementation of the Village Fund policy can improve the implementation of village autonomy. This can be seen in the implementation of the Village Fund policy which is carried out by involving the entire community from the formulation to the implementation of village development with an emphasis on the characteristics and potential of the Village.